THE EFFECTIVENESS OF USING ONLINE NEWSPAPER IN THE LEARNING OF GRAMMAR An Experimental Study at Eighth Grade Students of SMP Negeri 8 Batang (ELT Forum: Journal of English Language Teaching, 2016)
This research was conducted because there is a possibility to introduce online newspaper to the students to improve their ability in grammar mastery due to the rapidity of technology development. Online newspaper and grammar were chosen because online newspaper contains grammar which was written straightly correct because it will be read by all of people. The problem of this research is how effective the use of online newspaper in the learning of grammar is, and the purpose of this research is to find out whether it is effective or not. The subject of this research is eighth grade students of SMP Negeri 8 Batang. They were chosen because I had been experienced in teach them and know their grammar mastery is still low. The research design is quasi-experimental design, with post-test pre-test experimental and control group. The result of this research shows that the gain of experimental group score is not as high as control group. So, it can be concluded that using online newspaper in the learning of grammar is not effective because the score gain of experimental group is lower than control group. It was caused by the level of vocabularies used in online newspaper is not common in students’ daily language and they have different interests in topic of the online newspaper’s passage.